Participative and effective community leadership practice in Malaysia. - Mohamad, Madinah; Silong, Abu Daud; Hassan, Zaharah (2009)
This article discussed effective leadership from various theories. The dominant ideas on leadership initially begin with the traits theory, followed by behavior theory, situational theory and integrative theory. In analyzing these theories, one key theme emerged that contribute to effective leadership. It is the participative leadership style that was used in various forms such as the democratic, people-oriented and team leadership. Studies in Malaysia indicated that participative leadership is the key to a success of future public leadership in Malaysia. Ming-Yi Wu conducted comparative studies of participative leadership and concluded that it is culturally bound. There are differences between particpative leadership practiced in Taiwan, Japan and the United States. Furthermore, the researcher noted that most leadership studies are western biased, and thus there is a need to conduct studies in other cultures. This study focused on participative leadership among community leaders in Malaysia. It is based on a qualitative study, involving the in-depth interviews of eight Chairmen of Neighborhood Associations in Malaysia. The interview was recorded, transcribed verbatim, coded and analyzed into themes. One of the emerging themes from the findings relate to participative leadership. In conducting various leadership roles in the community, the leaders have to use the participative leadership approach in order to be more effective. However, the participation levels that the leaders can involve others in community efforts vary with situations.